Synthesis and cloning of long repeat sequences using single-stranded circular DNA - Bhuiyan, Afsana; Asakawa, Shuichi (Frontiers in Bioengineering and Biotechnology, 2023)
Non-coding repeat expansion causes several neurodegenerative diseases, such as fragile X syndrome, amyotrophic lateral sclerosis/frontotemporal dementia, and spinocerebellar ataxia (SCA31). Such repetitive sequences must be investigated to understand disease mechanisms and prevent them, using novel approaches. However, synthesizing repeat sequences from synthetic oligonucleotides is challenging as they are unstable, lack unique sequences, and exhibit propensity to make secondary structures. Synthesizing long repeat sequence using polymerase chain reaction is often difficult due to lack of unique sequence. Here, we employed a rolling circle amplification technique to obtain seamless long repeat sequences using tiny synthetic single-stranded circular DNA as template. We obtained 2.5–3 kbp uninterrupted TGGAA repeats, which is observed in SCA31, and confirmed it using restriction digestion, Sanger and Nanopore sequencing. This cell-free, in vitro cloning method may be applicable for other repeat expansion diseases and be used to produce animal and cell culture models to study repeat expansion diseases in vivo and in vitro.